US-China economic relations and impact on the world economy. Case study of Apple Inc. - Alkenov, Dayan; Černá, Iveta, 1979-; Hinčica, Vít; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The trade war between China and the United States creates problems in the supply chain and unforeseen risks for companies. Many corporations are forced to change their business strategies and relocate their manufacturing facilities. Apple was forced to relocate their main suppliers and find ways to deal with governments of China and the US. Research question is: How Apple Inc. was impacted by the trade war? As a result we can see that Apple was using its power over supplies to force them to move to countries of SouthEast Asia (India, Thailand, Vietnam), and was lucky to have TSMC moving its facilities to the US.
Vedoucí práce: Iveta Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses